Recruitment in Clinical Versus Community-Based Sites for a Pilot Youth Diabetes Prevention Program, East Harlem, New York, 2011-2012 - Nita Vangeepuram, MD, MPH; Kenya Townsend; Guedy Arniella, MS, LCSW (Centers for Disease Control and Prevention, 2016)
Introduction Little is known about successful strategies for recruitment of youth for research. The objective of this study was to compare clinical sites with community sites in the recruitment of teenagers for a new youth diabetes prevention program in East Harlem, New York. Methods We assessed diabetes risk for youth (aged 13-19 y) by measuring body mass index (BMI). We then screened overweight and obese youth for prediabetes using oral glucose tolerance testing, had them complete a health and lifestyle survey, and enrolled prediabetic youth into peer-led workshops. The recruitment strategies were 1) clinical referrals and 2) screenings at community sites. We compared the number of adolescents screened, the proportion eligible for testing, the proportion diagnosed with prediabetes, baseline characteristics, and the retention rates between those recruited in clinical and community sites. Results In 3 months, we completed BMI screening for 156 adolescents from community sites and 30 from clinical sites. Overall, 47% were at risk for diabetes on the basis of BMI, and 63% returned for diabetes testing; 35% had prediabetes, and 1 teenager had diabetes. Clinical sites yielded higher rates of diabetes risk on the basis of BMI and higher rates of return for screening and diagnosed prediabetes. Although demographics and BMI did not vary by recruitment site, we found differences in behaviors, self-efficacy, body image, and social support. There were no differences by recruitment site in workshop enrollment or completion or return for follow-up. Conclusion Both recruitment strategies were successful, and participants from both groups had high rates of undiagnosed prediabetes. Our approach allowed access to more adolescents and opportunities for education about diabetes in the community.